State Level Log Production Planning Using Linear Programming - Abdul Rahim, Abdul Rahman (1989)
This study aims to develop a log production planning model and to apply it at State-level planning. In the near future,Malaysia will have to rely more and more on the Permanent Forest Estate (PFE), after the State land forests have all been converted for agricultural development. A more efficient and effective log production planning model is essential to ensure that the forestry sector continues to contribute to the socio-econamic development of the country. A log production planning model (LPPM) was developed, consisting of a stand projection (STANDPROJ) model and a Linear Programming (LP) (LOGPROD) model. Data for the models were collected fran the State of Negeri Sembilan. STANDPROJ estimates forest yield which are used, together with forest areas am forest management policies, to generate an LP problem matrix in LOIUS spreadsheet. The matrix is accessed am solved by an LP optimizer. The optimizer also transmits the solution back to LOIUS which acts both as a matrix generator and report writer.